2008
DOI: 10.1002/chem.200800890
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoric Acid Catalyzed Enantioselective Transfer Hydrogenation of Imines: A Density Functional Theory Study of Reaction Mechanism and the Origins of Enantioselectivity

Abstract: The phosphoric acid catalyzed reaction of 1,4-dihydropyridines with N-arylimines has been investigated by using density functional theory. We first considered the reaction of acetophenone PMP-imine (PMP=p-methoxyphenyl) with the dimethyl Hantzsch ester catalyzed by diphenyl phosphate. Our study showed that, in agreement with what has previously been postulated for other reactions, diphenyl phosphate acts as a Lewis base/Brønsted acid bifunctional catalyst in this transformation, simultaneously activating both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
114
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 80 publications
9
114
0
2
Order By: Relevance
“…We recently reported a density functional theory study on the mode of action of diarylphosphoric acid organocatalysts in the transfer hydrogenation of ketimines using Hantzsch esters as hydrogen donors. [7] Our results showed that diarylphosphoric acids act as bifunctional Lewis base/Brønsted acid (LBBA) catalysts.[8] Moreover, we showed that both E and Z iminium (presumably in equilibrium under the reaction conditions) species are competent substrates for the hydride transfer. Following imine protonation, the resulting phosphate engages in two hydrogen bonds, one with the iminium and one with the N À H group of the dihydropyridine.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…We recently reported a density functional theory study on the mode of action of diarylphosphoric acid organocatalysts in the transfer hydrogenation of ketimines using Hantzsch esters as hydrogen donors. [7] Our results showed that diarylphosphoric acids act as bifunctional Lewis base/Brønsted acid (LBBA) catalysts.[8] Moreover, we showed that both E and Z iminium (presumably in equilibrium under the reaction conditions) species are competent substrates for the hydride transfer. Following imine protonation, the resulting phosphate engages in two hydrogen bonds, one with the iminium and one with the N À H group of the dihydropyridine.…”
mentioning
confidence: 98%
“…For instance, in our previous study we calculated that protonation of a PMP ketimine has a barrier smaller than 2 kcal mol À1 . [7] Therefore, the barrier for enamine protonation should not be much higher. The enantioselectivity is thus determined in the hydride transfer step.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Organocatalytic transfer hydrogenation using dihydropyridines as hydride donors and Brönsted acid catalysis has also been intensively investigated. 21,22 Sasson et al reported in 2000 that Pd/C, Zn combination in water in presence of organic hydrogen acceptors (benzaldehyde, nitrobenzene or 4-nitroanisole) acts as a direct hydrogen transfer from water to an organic substrate, giving the reduction product. 23 However, this methodology had not been explored in any depth using other hydrogen donors and substrates.…”
Section: Introductionmentioning
confidence: 99%